Analysis of the content of the human geography book for the sixth grade according to the economic dimension of sustainable development - Salman, Zainab D.; Jalab, Hana Khudair (Al-Adab Journal, 2022)
The current research aims to analyze the human geography book for the sixth literary grade according to the economic dimension of sustainable development. The researcher used a questionnaire for the sub-indicators of the economic dimension of sustainable development, which was developed by the UNESCO International Organization for Education and in line with the Iraqi educational environment. The questionnaire consisted of (17) sub-indicators of the economic dimension of sustainable development. The researcher, the content of the book of human geography for the sixth literary grade according to the economic dimension of sustainable development in the light of the questionnaire that was prepared and included the analysis of the content of the book of geography at a rate of (164) pages.Statistical analysis on the availability of the economic dimension in rank B A fact (127) recurring, with a percentage of (63.5%).